Potentials of open lawn towards enhancing user experience in urban park - Shahriffin, Nur Alina; Zakariya, Khalilah (KAED, IIUM, 2016)
Nowadays, the urban area is lacking of green spaces due to the rapid development. Most of what we can see today are buildings rather than green spaces. Consequently, the creation of open lawn becomes one of the alternative to recover the lack of green spaces in urban area. Open lawn is important for the city dwellers because it consists of natural grass that can give benefits to the environment, physical and mental health and can trigger senses of the users. However, the function of open lawn nowadays are more for the passive activities due to the texture and there is no interesting factors that can trigger user’s senses. Thus, the aim of the study is to determine the effect of open lawn on user activities and senses in the urban park. There are two urban parks in Shah Alam have been selected as case studies and 30 respondents have participated in the survey questionnaire. Other than the survey questionnaire, data is gathered using direct observation on the chosen sites to identify the potentials and constraints. From the findings, this study identifies that open lawn has potentials to offer peaceful and calm senses, and a feeling of freedom and safety to the visitors. The recommendations propose the open lawn to have more interesting and playful character to trigger user experience and senses.